An explanation for the peculiar periphery of supernova remnant G309.2–0.6. (August 2018) - Yu, Huan; Fang, Jun
Abstract: Supernova remnant (SNR) G309.2–0.6 has a peculiar radio morphology with two bright ears to the southwest and northeast, although the main shell outside the ears is roughly circular. Based on an earlier proposal that the supernova ejecta has a jet component with extra energy, the dynamical evolution of the remnant is solved using 3D hydrodynamical (HD) simulation to investigate the formation of the periphery of the remnant. Assuming the ejecta with a kinetic energy of 10 51 erg and a mass of 3 M ⊙ evolved in a uniform ambient medium for a time of ∼ 4000 yr and the jet component has cylindrical symmetry with a half open angle of 10°, the result indicates that the energy contained in the jet is about 10%–15% of the kinetic energy of the entire ejecta to reproduce the detected profile. This study supports that the remnant originated from a jet-driven core-collapse supernova.